Mandela: The Untold Heritage. Issue 6 (2nd November 2019) - Mangcu, Xolela
Abstract : This article argues that existing biographies of Nelson Mandela are constructed on archaic colonial stereotypes of African societies as 'tribes', 'premodern' and 'pagan'. In none of the biographies do we learn anything about such vital aspects of Mandela's life story as his Thembu royal family's pragmatic policy of co-operation with colonial governments, the centrality of the quasi-parliamentary body known as the United Transkei Territories General Council, popularly known as the Bhunga (Council) in the life of the Transkei, and his family's leadership role in that body, including that of his father, Gadla. The biographies are also based on incorrect attributions of his ethnic identity and the place of his family in the Thembu royal hierarchy. Mandela's corrections of these misrepresentations were left out of his autobiography, Long Walk to Freedom, and he was quoted as saying the opposite of those corrections. These editorial practices pose troubling questions for the credibility and integrity of the Mandela archive.